2011
DOI: 10.1039/c0cc02403a
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cope-type hydroamination reactivity of hydrazine derivatives

Abstract: A systematic investigation on the metal-free, Cope-type hydroamination reactivity of hydrazides and analogues is reported. Optimization of the hydrazide structure resulted in more facile intramolecular reactivity and enabled intermolecular reactions of alkenes, thus providing a direct approach to polysubstituted hydrazides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…amines) on N -isocyanates would be essentially irreversible. Building on our expertise in metal-free hydroamination reactions of hydrazine derivatives, 10 we developed an N -isocyanate addition/Cope-type hydroamination cascade for the formation of saturated nitrogen heterocycles (eqn (2)), illustrated below using blocked N -isocyanate 1a . 7 …”
Section: Resultsmentioning
confidence: 99%
“…amines) on N -isocyanates would be essentially irreversible. Building on our expertise in metal-free hydroamination reactions of hydrazine derivatives, 10 we developed an N -isocyanate addition/Cope-type hydroamination cascade for the formation of saturated nitrogen heterocycles (eqn (2)), illustrated below using blocked N -isocyanate 1a . 7 …”
Section: Resultsmentioning
confidence: 99%
“…Niemeier and Kjell (2013) reported that dilution plays an important role in increasing the intrinsic safety of aqueous hydrazine. Aqueous hydrazine, instead of hydrazine, is thus used as a blowing agent (Berins, 2002) and a precursor to make various high-value chemicals widely (Loiseau et al, 2011;Silva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…18 However, these metal-catalyzed hydroamination methodologies have various limitations such as harsh basic conditions, the requirement of a directing group, and limited substrate scopes. Two additional approaches from the Studer 19 and Beauchemin 20 groups accomplish this transformation through free radical and pericyclic additions, respectively, although selectivity is substrate-dependent in the latter case. 21 Despite considerable advances in the area of metal-catalyzed anti-Markovnikov hydroaminations of olefins, a general method remains an elusive goal.…”
Section: Introductionmentioning
confidence: 99%